Ergonomic Assessment of Driver Posture in Prototype Vehicles for Kontes Mobil Hemat Energi (KMHE) Using CATIA - Afnison, Wanda; Khairul, Farid; Irzal, Irzal; Milana, Milana (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
The ergonomic design of the cockpit is crucial for improving driver comfort and safety, particularly in prototype vehicles for energy efficiency competitions. This study evaluates the driver’s body posture using the Rapid Upper Limb Assessment (RULA) technique to propose design improvements that support better posture and reduce physical strain. The research methodology includes analyzing musculoskeletal risk levels through RULA, supported by the Human Activity Analysis tool in CATIA. The evaluation was conducted on the FT UNP prototype car in the Kontes Mobil Hemat Energi (KMHE), revealing a RULA score of 6, indicating a high risk of musculoskeletal issues. The findings suggest the need for redesigning the cockpit to enhance posture, including adjustments to the seat tilt, steering wheel position, and pedals. These ergonomic improvements are expected to reduce driver fatigue, enhance performance, and minimize injury risks.